Analisis Pengaruh Persepsi Kualitas Produk, Kepercayaan Terhadap Merek, dan Ewom Terhadap Keputusan Pembelian Konsumen di Shopee - Barkhoya, Muhammad Alfin; Vania, Amelindha (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to analyze the effect of perceived product quality, brand trust, and electronic word of mouth (EWOM) on consumer purchasing decisions on the Shopee e-commerce platform in Malang City. With an explanatory quantitative approach, data were collected using purposive sampling method and analyzed through Structural Equation Modeling (SEM) technique. The results showed that EWOM has the most significant direct influence on purchasing decisions with a path coefficient of 0.45, followed by brand trust (0.38) and perceived product quality (0.42). The indirect influence mechanism of the three variables is also prominent, highlighting the complexity of the interaction of these factors in shaping consumer purchasing decisions. The valence dimension of EWOM and product functionality are the main indicators that influence consumer preferences. This research provides practical insights for businesses to improve marketing strategies through increasing online reviews, building brand trust, and optimizing product quality. The theoretical implications enrich the literature on consumer behavior in the evolving e-commerce ecosystem.